Approach bias modification in food craving: a proof-of-concept study - Brockmeyer, Timo; Küppers, Carolyn; Reetz, Christina; Schmidt, Ulrike; Friederich, Hans-Christoph (European eating disorders review, 2015)
The aim of the present proof-of-concept study was to test a novel cognitive bias modification (CBM) programme in an analogue sample of people with subclinical bulimic eating disorder (ED) psychopathology. Thirty participants with high levels of trait food craving were trained to make avoidance movements in response to visual food stimuli in an implicit learning paradigm. The intervention comprised ten 15-minute sessions over a 5-week course. At baseline, participants showed approach and attentional biases towards high-caloric palatable food that were both significantly reduced and turned into avoidance biases after the training. Participants also reported pronounced reductions in both trait and cue-elicited food craving and in ED symptoms as well. The overall evaluation of the training by the participants was positive. The specific CBM programme tested in this pilot trial promises to be an effective and feasible way to alter automatic action tendencies towards food in people suffering from bulimic ED psychopathology. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.
Gesehen am 29.05.2020